2021
DOI: 10.3390/ani11061560
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Reveals Intestinal Pathogenesis and Self-Repair in Rabbits Fed an Antibiotic-Free Diet

Abstract: The prohibition of the use of growth-promoting drug additives in feeds was implemented in China in 2020. However, rabbits can experience symptoms of intestinal disease, such as diarrhea and flatulence, when switching from standard normal diets with antibiotics to antibiotic-free diets. The molecular mechanisms related to the occurrence of these diseases as well as associated physiological and metabolic changes in the intestine are unclear. Thus, the objectives of this study were to study the pathogenesis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…In addition, the phenylalanine, tyrosine, and tryptophan biosynthetic pathways are necessary for the production of aromatic amino acids, including tryptophan and phenylalanine. Inactivity in this pathway disturbs intestinal metabolism and promotes intestinal inflammation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the phenylalanine, tyrosine, and tryptophan biosynthetic pathways are necessary for the production of aromatic amino acids, including tryptophan and phenylalanine. Inactivity in this pathway disturbs intestinal metabolism and promotes intestinal inflammation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, the harm caused by HS to the human body is a dynamic process that can fluctuate with time and intensity; the outcomes may change depending on the research settings. Furthermore, HS may operate as the initial messenger to regulate inositol molecule, insulin signal, amino acid metabolism, and glucose metabolism network and respond to and heal body damage ( Tang et al, 2021 ; Wen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabonomics is a technique for identifying and quantifying all metabolites present in biological samples. At present, Tang et al (2021) used non-targeted metabonomics to reveal the intestinal pathogenesis and self-healing of rabbits without antibiotic diet, He et al (2019a) used fecal metabonomics technology to explore the metabolic changes of heat stress in late pregnancy of primiparous sows, and Wen et al (2021) used metabonomics technology to explore the metabolic changes of heat stress on cecal contents of mice. However, the research on the relationship between heat stress and rabbit intestinal microbial ecosystem and its metabolites is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the experiment, 6 rabbits from the normal condition were selected as the control group (Con, n = 6) and 6 rabbits from the disease condition (diarrhea) were selected as the experiment (diarrhea) group (Dia, n = 6) according to their weight, physiological condition and health status [ 26 ]. Each rabbit was fed 150–200 g diet per day and lived separately in a clean cage (600 × 600 × 500 mm, 21–23 °C, 60–75 % humidity, 14 h light (60 lx)) [ 20 ]. These animals had free access to fresh water.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in mice have shown that gut microbes do not immediately return to normal when antibiotics are stopped, and were limited to the large intestine or small intestine [ 19 ]. The content of amino acids (Anthranilic acid, L-Tryptophan, and L-Phenylalanine) in a diarrhea group of rabbits fed without antibiotics was higher than that in a normal group [ 20 ]. Previous studies have shown that the use of antibiotics changes the link between intestinal microbes and amino acid metabolism [ 21 ].…”
Section: Introductionmentioning
confidence: 99%